Development and validation of a questionnaire to assess Unaccompanied Migrant Minors' needs (AEGIS-Q). (11th November 2020) - Di Pietro, Maria Luisa; Zaçe, Drieda; Sisti, Leuconoe Grazia; Frisicale, Emanuela Maria; Corsaro, Alice; Gentili, Andrea; Giraldi, Luca; Bruno, Stefania; Boccia, Stefania
Abstract: Background: While many studies focus on specific aspects of Unaccompanied Migrant Minors' (UMMs) health, especially mental well-being, there is a lack of tools comprehensively assessing their needs. To fill this gap, we developed and validated a questionnaire to thoroughly assess unAccompaniEd miGrant mInorS' physical, psychological, legal, spiritual, social and educational needs (AEGIS-Q). Methods: This work consisted of three stages. The first one involved an extensive literature review. Given the results of the review, a first draft of the questionnaire was developed and submitted to a panel of experts for validation (Delphi method-second stage). During the third stage, the final version of the questionnaire was pilot-tested in a sample of 18 UMMs. Results: The questionnaire, drafted based on the results of the review, consisted of sections covering personal data, migration profile, physical health needs and access to healthcare, psychological needs, legal needs, spiritual needs and educational and social needs of UMMs. After two Delphi rounds, the final version of the questionnaire, consisting of 83 questions, was structured. The pilot study had a response rate of 89–100%. We found substantial reliability for most of the sections in the questionnaire, including physical health (α=0.652), legal (α=0.781), and educational and social (α=0.614) needs. The questions regarding psychological needs had very high reliability (α=0.860). Conclusions: The questionnaire offers a useful sharable tool to assess and monitor UMMs' needs, helping the reception system to better know and meet their needs and implement the taking in charge.